2005
DOI: 10.1080/09638280500030688
|View full text |Cite
|
Sign up to set email alerts
|

Functional performance and quality of life related to training and detraining of community-dwelling elderly

Abstract: One-month detraining was enough to show functional decline, with gait speed the most sensitive parameter to detect these changes and QL measure most resilient, beneficial factor during the detraining process. Based on these findings, it is recommended that programmes devised for elderly should not be interrupted, to maintain the acquired benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
21
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 26 publications
8
21
1
2
Order By: Relevance
“…However, not much research has been conducted on the effects of detraining adaptations with regard to different training modes and physical performance (28), although a number of recent studies focused on detraining have been based on a program of combined resistance and endurance training (4,8,(35)(36)(37). Moreover, although numerous studies have also focused on obese subjects or seniors (2,8,27,37,39,40), less is known concerning changes in body weight with regard to intervention research focusing on young men (25), particularly comparing the responses to resistance vs. endurance training (28,31).…”
Section: Introductionmentioning
confidence: 99%
“…However, not much research has been conducted on the effects of detraining adaptations with regard to different training modes and physical performance (28), although a number of recent studies focused on detraining have been based on a program of combined resistance and endurance training (4,8,(35)(36)(37). Moreover, although numerous studies have also focused on obese subjects or seniors (2,8,27,37,39,40), less is known concerning changes in body weight with regard to intervention research focusing on young men (25), particularly comparing the responses to resistance vs. endurance training (28,31).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, despite evidence of physiological decline during detraining, there is not enough data suggesting how long the beneficial effects of training are maintained, how this affects the health related quality of life (HRQoL) and how functional fitness changes following the cessation of exercise intervention in institutionalized elders [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that people with a higher frequency of falls have greater sway velocity and greater anteroposterior (AP) displacement during quiet standing (Fernie, Gryfe, Holliday, & Llewellyn, 1982;Maki, Holliday, & Topper, 1994). Gait has been documented as a sensitive predictor of fall risk, frailty, and functional decline (Riley, DellaCroce, & Kerrigan, 2001;Teixeira-Salmela et al, 2005;Winter, Patla, Frank, & Walt, 1990;Wong, Wong, Pang, Azizah, & Dass, 2003;Woo, Ho, Lau, Chan, & Yuen, 1995). Specifically, spatiotemporal gait parameters such as gait velocity, stride length, cadence, double support time, swing time, and the coefficients of variation (CV) for stride length and swing time are predictors of fall risk in older adults (Callisaya et al, 2011;Callisaya, Blizzard, Schmidt, McGinley, & Srikanth, 2010;Hausdorff et al, 2001).…”
mentioning
confidence: 99%